Permanent pacemaker implantation after Alcoholic Septal Ablation: long-term outcomes. (19th May 2022) - Grazina, A; Aguiar Rosa, S; Fiarresga, A; Garcia Bras, P; Ferreira, V; Cardoso, I; Viegas, JM; Ramos, R; De Sousa, L; Oliveira, M; Cacela, D; Cruz Ferreira, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Patients with hypertrophic obstructive cardiomyopathy (HOCM) that remain symptomatic despite optimized medical therapy are often submitted to alcohol septal ablation (ASA). One of the most frequent complications is the complete heart block (CHB), requiring permanent pacemaker (PPM) in variable rates, up to 20% of the patients. The long-term impact of PPM implantation in these patients remains unclear. Objectives: This study aims to evaluate the long-term pacemaker dependency in patients with PPM after ASA and to assess the long-term impact of PPM in these patients. Methods: In a tertiary center, patients who underwent ASA were retrospectively analyzed. Patients with previous PPM or implantable cardio-defibrillator were excluded. The groups with and without PPM implantation after ASA were compared regarding baseline characteristics, procedure data and outcomes. In the group who implanted PPM, the long-term pacing rates were evaluated. Results: Between 2009 and 2020, 109 patients underwent ASA. 97 patients were included in this analysis (68% female, mean age 65.2 years-old). 16 patients (16.5%) required PPM implantation for CHB. In those, no vascular access, pacemaker pocket or pulmonary parenchyma complications were noted. The baseline characteristics regarding co-morbidities, symptoms, echocardiographic and electrocardiographic findings were identical in the two groups, with statistically significant differences in the mean age (70.6y/o in the PPM group versus 64.1y/o) and in the beta-blocker therapy rates previously to the intervention (56% in the PPM group versus 84%). Procedure-related data showed higher creatine kinase (CK) peaks in the PPM group (1692U/L versus 1243U/L, p0.05), without significant differences in the alcohol dose (2.1ml in both groups, p0.33). In the PPM group, the mean pacing rates at 1 month, 1 year and 2 years were 66.6±38.0, 50.4±44.1 and 50.8±42.5, respectively, with 2 patients (12.5%) having 1-5% pacing and none having pacing <1% at 2 years. In the group without PPM, 5 patients (6.2%) required posteriorly PPM implantation during the follow-up. There were no statistically significant differences in the two groups regarding in-hospital mortality, 1 year mortality or 1 year re-hospitalization. Despite a lower mean follow-up period in the PPM group (2.3±1.5 years versus 3.5±2.2 years, p0.05), there were no differences in the groups regarding all-cause mortality, cardiac cause mortality and cardiac cause re-hospitalization, with a statistical tendency to a lower all cause re-hospitalization in the PPM group (19% versus 43%, p0.07). Conclusions: The registered pacing rates shows that all devices were adequately implanted. The long-term impact analysis suggests that the outcomes in patients who implant PPM after ASA are non-inferior to those who do not, with a tendency to reduce all cause re-hospitalizations.